Development of iOS/Android apps for scientific computation - Lim, Ming (2018)
Mobile applications relating to numerical computations have not been studied or developed extensively due to the nature and complexity of the topic. Applications like these usually require the use of numerical libraries to simplify the implementation process of complex mathematical computations. As there are many libraries available for use, the performance of the libraries will be experimented to allow programmers have an idea of which library is more efficient to use for real life applications such as generating 3D computer graphics, economic calculations or encrypting messages. In this report, a mobile application on scientific computations including matrix and graphing functions will be developed and a speed test will be conducted for the matrix libraries. This report will also present the implementation process of the proposed functions using a few different libraries, and an evaluation of each library’s performance will be discussed.